The Buddha’s Paṭiccasamuppāda: Addressing contemporary environmental development challenges through eschatological perspectives - Johannes, Hendro Putra (Institute for Advanced Science Social, and Sustainable Future, 2025)
Background: Religion is often considered as a cause of environmental problems. In response to this pessimism, Buddhism through the philosophy of Dharma comes up as revolutionary perspective in shaping contemporary environmental development paradigm, a counter for modern Cartesian-Newtonian paradigm. This philosophy is embodied in the concept of paṭiccasamuppāda applied as “scalpel” on existing environmental problems. Mehods: This study employs a qualitative approach using library research, analyzing philosophical, religious, and environmental texts. Through content analysis of Buddhist teachings, particularly paṭiccasamuppāda, the study explores its role as an alternative paradigm for addressing environmental challenges. Findings: The findings reveal that paṭiccasamuppāda, or the law of dependent origination, provides a holistic understanding of the interconnectedness between humans and nature. Unlike the Cartesian-Newtonian paradigm, which separates the observer from the observed, paṭiccasamuppāda emphasizes relational existence and balance, fostering ecological ethics based on interdependence. This perspective reduces environmental exploitation and encourages sustainable practices. Conclusion: The study concludes that paṭiccasamuppāda serves as a transformative framework for addressing contemporary environmental issues. By shifting from a dualistic worldview to an interconnected one, it promotes a sustainable development model. Integrating Buddhist ecological ethics into environmental policies and education can contribute to a more sustainable future. Novelty/Originality of this article: This study presents paṭiccasamuppāda as a fundamental principle for reinterpreting environmental sustainability. Unlike previous research that broadly discusses Buddhist ethics, this study specifically highlights paṭiccasamuppāda as a precise analytical tool for addressing environmental issues. By bridging Buddhist philosophy and contemporary ecological challenges, this study offers a novel perspective on sustainability rooted in spiritual wisdom.